Technical Analysis and Overview of the Concepts of Organizational studies with special Emphasis on Behavior, Theory, and Ecology - Chopra, Kamal Nain (Journal of Organizational Psychology, 2018)
The studies related to the Concepts of Organizational studies have been reviewed and discussed. Special emphasis has been placed on Behavior, Theory, and Ecology, of Organizational Studies. The paper is expected to be useful to the new entrants in the field and also the senior organizational experts and advisors in the firms. The Technique of Simulation for optimization of learning in Organization has been discussed.